QCD phase structure from functional methods - Gao, Fei; Pawlowski, Jan M. (Physical review, 2020)
We discuss the QCD phase structure at finite temperature and chemical potential for 2-flavor and 2+1-flavor QCD. The results are achieved by computing QCD correlation functions within a generalized functional approach that combines Dyson-Schwinger equations (DSE) and the functional renormalization group (fRG). In this setup fRG precision data from [A. K. Cyrol, M. Mitter, J. M. Pawlowski, and N. Strodthoff, Phys. Rev. D 97, 054006 (2018).] for the vacuum quark-gluon vertex and gluon propagator of 2-flavor QCD used as input, and the respective DSEs are expanded about this input. While the vacuum results for other correlation functions serve as a self-consistency check for functional approaches, the results at finite temperature and density are computed, for the first time, without the need of phenomenological infrared parameters.
Gesehen am 24.09.2020